Carotid artery stenting and improvement of cognitive function in patients with asymptomatic carotid artery stenosis - Jácome,Filipa (2024)
Abstract Introduction: Several studies unveiled an association between asymptomatic carotid artery stenosis and cognitive impairment, questioning the “asymptomatic” nature of carotid stenosis. Although there is increasing evidence of the impact of carotid artery stenting (CAS) on cognition, the current literature still contains some unclear data and conflicting results. This study aimed to examine the impact of CAS on various domains of cognitive function in patients with asymptomatic carotid artery stenosis. Methods: Studies published up to February 2023 that evaluated cognitive function in patients with asymptomatic carotid artery stenosis who underwent CAS were searched in PubMed and Scopus databases. All original studies assessing pre- and post-operative cognitive functions in patients with asymptomatic carotid stenosis undergoing CAS were considered eligible for inclusion. Editorials, letters, case reports, review articles, and animal studies were excluded. Results: A total of 1155 articles were identified in our search. After screening, 12 studies were eligible for our review, including 273 CAS in asymptomatic patients. Eleven articles were prospective cohort studies, and one was a randomized controlled trial. The mean age of included patients was 70.1%3.4 years, and approximately 63% of patients were male (n=170 male patients), although two studies did not mention gender. Only seven articles reported the type of anesthesia, and locoregional techniques were used in all cases. Regarding cerebral protection, in eight studies, a distal filter was used; one study used flow reversal; in another, no protection device was used; three studies did not mention if any technique for cerebral protection was used during the procedure. Conclusion: The included studies on cognitive performance after CAS exhibit wide variations in the timing of assessment, specific tests performed, and the use of cerebral protection devices. Additionally, the study populations are small, and several possible confounding factors exist. Thus, a limitation in the analysis is evident, and several attempts to assess the effect of CAS on cognitive function have yielded conflicting conclusions. The debate over the optimal management of asymptomatic carotid patients is ongoing.